2014
DOI: 10.3329/bjvm.v11i2.19140
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological characterization of anthrax spore vaccine in goat

Abstract: Anthrax is caused by Bacillus anthracis bacterium and an acute infectious febrile septicemic disease of all warm-blooded animals including human. It is a disease of major economic importance in ruminant specially in goat characterized principally by a rapid fatal course followed by sudden death. The present investigation was under taken to determine the biochemical characterization of anthrax spore vaccine bacteria and to determine the immunological response in goat after anthrax vaccination. Anthrax vaccine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
3
10
1
Order By: Relevance
“…Anything that alters the replication of the organisms in the body can cause altered immune response induced by the vaccine as well as render the vaccine become ineffective (CDC website). However, our findings strengthen the findings of Dipti et al (2013) and Roy et al (2013) who conducted the research works up to 90 days. In this study we report the results for an extended period of time upto one year.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Anything that alters the replication of the organisms in the body can cause altered immune response induced by the vaccine as well as render the vaccine become ineffective (CDC website). However, our findings strengthen the findings of Dipti et al (2013) and Roy et al (2013) who conducted the research works up to 90 days. In this study we report the results for an extended period of time upto one year.…”
Section: Resultssupporting
confidence: 89%
“…Vaccination response as obtained in this study differed from the finding of Dipti et al (2013) and Roy et al (2013) although they used same vaccine that we used in our study, who could detect early immune response in cattle at day 30 of immunization; whereas, in the present study we revealed early response at day 7 of post-vaccination. In addition, Dipti et al (2013) described a steady increase in antibody level upto 90days.…”
Section: Resultscontrasting
confidence: 76%
“…The CFT results indicated that the production of specific antibodies induced by vaccination with Sterne 34F 2 did not persist over a long period of time in cattle. In many studies, conducted in cattle and goats, the antibody response following vaccination against anthrax was monitored using a PA-based ELISA, currently accepted as the best serological procedure, and different antibody kinetics were observed ( Dipti et al, 2013 ; Roy et al, 2013 ; Hassan et al, 2015 ). However, the comparison of serological data is very difficult since many factors affect the immune response of animals, such as the vaccine type, the age of vaccination and, mostly, the health status of animals ( IOWA Beef Center website, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a single dose of Sterne vaccine may not be sufficient to ensure protective immunity in the animal to last for a year, and more than one initial dose of the Sterne vaccine may be necessary ( Turnbull et al, 2004 ; Mongoh et al, 2008 ; World Health Organization [WHO], 2008 ). However, very few studies focusing on immunological characterization have been conducted with cattle and goats ( Dipti et al, 2013 ; Roy et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many exploratory studies were performed in Bangladesh to find out the reasons of repeated outbreaks of anthrax, and many of them have suggested measures to control the disease. Most of the studies agreed that limited vaccination coverage was one of the most important contributing factors, and studies recommended that regular effective vaccination may reduce anthrax infection [ 18 , 19 , 20 , 21 ]. Anthrax vaccine for livestock is available in Bangladesh and manufactured by the Livestock Research Institute (LRI, Dhaka, Bangladesh), a government-regulated and -owned institute under the Ministry of Fisheries and Livestock.…”
Section: Introductionmentioning
confidence: 99%